2020
DOI: 10.1111/head.13761
|View full text |Cite
|
Sign up to set email alerts
|

Headache at the Chronic Stage of Ischemic Stroke

Abstract: Background Headache in ischemic stroke survivors after the acute stage is incompletely described. Objective We aimed to prospectively describe the characteristics of headache and the predictors of headache at the chronic stage after ischemic stroke. Methods We conducted a prospective observational cohort study including 102 acute ischemic stroke patients admitted to a Stroke Unit. Patients were interviewed at the acute and the chronic stage (12 months after stroke). Characteristics of those headaches were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…The occurrence of persistent headaches in our study was 10.4%, which is in accordance with previous studies [ 5 , 6 ]. However, only 1% of persistent headaches after stroke was found in a study which included persistent headaches at the chronic stage of ischemic stroke, average follow-up time was 15.6 months [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The occurrence of persistent headaches in our study was 10.4%, which is in accordance with previous studies [ 5 , 6 ]. However, only 1% of persistent headaches after stroke was found in a study which included persistent headaches at the chronic stage of ischemic stroke, average follow-up time was 15.6 months [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed a higher prevalence of tension-type headaches [ 5 – 8 ]. One study demonstrated changes in characteristics of headaches from migraine-type to tension-type in almost half of stroke survivors at the chronic stage of ischemic stroke [ 7 ]. The authors of this study suspected that stroke had a modulating effect on the headache in most stroke survivors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be explained by our less severely affected stroke population. Post-stroke headache associated with ischemic stroke is poorly understood, only occurring in ~14% of patients ( 19 , 20 ). This underscores the importance to further explore headache associated with ischemic stroke to inform patient management.…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of stroke are often debilitating and result in permanent disability for the stroke survivor. Some survivors experience physical symptoms such as aphasia, dysphagia, headaches, increased muscle tone, contractures, spasticity, hemiparesis, facial palsy, mobility, and balance issues (Carvalho Dias et al, 2020; Costa et al, 2016; Persson et al, 2020). Others may deal with cognitive and emotional impairments from direct damage to the brain.…”
mentioning
confidence: 99%